The Efficacy of PEGylated Nanocarrier Extract of Red Ginger (Zingiber officinale var. sunti Valeton) and Lemongrass (Cymbopogon citratus) Combination on Fasting Blood Glucose and HbA1c Levels in Diabetes Mellitus Model Rats - Widayanti; Eka Hendryanny; Lelly Yuniarti (Global Medical & Health Communication (GMHC), 2025)
Diabetes mellitus is a major global public health problem due to its serious complications. In addition to standard pharmacological therapy, herbal-based interventions are increasingly explored as complementary approaches to improve glycemic control. This study aimed to evaluate the effects of a PEGylated nanocarrier extract combining red ginger (Zingiber officinale var. sunti Valeton) and lemongrass (Cymbopogon citratus) on fasting blood glucose and HbA1c levels in a diabetes mellitus rat model. An experimental randomized controlled study was conducted from May to August 2024 at the Pharmacy Laboratory of Universitas Islam Indonesia, Yogyakarta, and the Food and Nutrition Laboratory of Universitas Gadjah Mada, Yogyakarta. Experimental rats were randomly allocated into six groups: a healthy control group, a negative control group, a positive control group receiving glibenclamide (0.45 mg/kg body weight) and simvastatin (0.9 mg/kg body weight), and three treatment groups administered the PEGylated nanocarrier ginger lemongrass extract orally at doses of 20, 40, and 80 mg/kg body weight/day. Fasting blood glucose levels were measured using a GOD-PAP method, while HbA1c levels were assessed by immunoassay. Data were analyzed using one-way ANOVA followed by Tukey post hoc testing. The results demonstrated that the treatment group receiving 80 mg/kg body weight/day showed the most significant reductions in fasting blood glucose (172.44±4.49 mg/dl) and HbA1c (3.79±0.15%). These reductions were statistically significant compared with the control groups (p<0.001). In conclusion, the PEGylated nanocarrier combination of red ginger and lemongrass significantly improved glycemic parameters in diabetic rats. This formulation may represent a potential complementary strategy for glycemic control, supporting further investigation in mechanistic and translational studies before clinical application.